Analisis Perubahan Tutupan Lamun Dengan Menggunakan Data Citra Satelit Di Pulau Barrang Lompo Kota Makassar - Hadi, Farhansyah Noer; Rauf, Abdul; Yunus, Muhammad (JURNAL ILMIAH WAHANA LAUT LESTARI (JIWaLL), 2024)
ABSTRACK Barranglompo Island has an area of about 20.64 ha located about 12 kilometers west of Makassar City and is in the Spermonde Islands region. Seagrass is one of the important ecosystems in coastal areas. Seagrass ecosystems play an important role as producers in coastal food webs (Susetino, 2004 in Trisnawati, 2012). Ecologically seagrasses have several important functions in coastal areas, they are an important food source for many organisms (in the form of detritus) Anurogo, W. et al., 2018). Remote sensing techniques utilizing Landsat 8 satellite imagery can provide many advantages for use in seagrass mapping to determine the extent of seagrass distribution. The results of mapping seagrass distribution on Barrang Lompo Island using the Lyzenga method showed that the area of seagrass ecosystem on Barrang Lompo Island decreased every year by 29.95 Ha. Where in the 2013 map has an area of 50.24 Ha, while in the 2021 map the seagrass ecosystem area is 20.29 Ha.